'You can't repeal regret': targeting men for mobilisation in Ireland's abortion debate. (1st September 2021) - Hunt, Kate; Friesen, Amanda
Abstract : This study explores how social movement organisations involved in the abortion debate in the Republic of Ireland attempted to appeal to men in their campaign messages before the 2018 referendum on the Eighth Amendment concerning abortion. We scrape social movement organisations' Twitter accounts to conduct quantitative and qualitative content analyses of images and videos the organisations posted, and find evidence that social movement organisations sometimes extended their frames to men as voters. Social movement organisations evoked themes of hegemonic masculinity in their imagery and messaging, though these themes were not a large portion of overall campaign tweets and there were distinct differences in how this was done by the two organisations we study. Previous research suggests anti-abortion organisations extend their frames to incorporate 'pro-woman' messaging. Our research contributes by exploring the ways that frames may be extended by both anti- and pro-abortion actors to target men and mobilise masculinity in public debates over women's rights.